Characterization of H9N2 avian influenza virus isolated from chickens and waterfowl in parts of Southern China from 2018 to April 2024 - Wanting Zhou; Jun He; Fangfang Qiao; Mengyao Wang; Qinghang Zeng; Yang Liu; Yue Zhao; Liji Zhang; Ting Li; Shouwen Du; Minhua Sun; Ming Liao (Poultry Science, 2025)
The H9N2 subtype of avian influenza virus (AIV) has become endemic in poultry farms across China, providing internal genes for other subtypes of viruses and occasionally having the ability to infect humans, thereby posing a significant public health threat. In this study, 61 H9N2 viruses were isolated from chickens and waterfowl in Southern China between 2018 and April 2024. We characterized their genetic derivation, antigenic diversity, receptor-binding specificity, neuraminidase (NA) activity, replication, and transmission in chickens and systematic pathological analysis. Genetic analysis revealed that 60 isolates belonged to the h9.4.2.5 lineage, while 7, 20, and 33 H9 strains belonged to the h9.4.2.5a, b, and c branches, respectively. One isolate belonged to the h9.4.2.1 lineage. Mainly tested H9N2 strains preferentially bound to human-type receptors, except one virus exhibiting dual receptor-binding specificity. Antigenicity analysis indicated that these tested viruses could be classified into 2 separate antigenic clusters. In addition, the selected viruses efficiently replicated and transmitted in chickens at a high dose induction. Continuous and systematic surveillance of H9N2 virus mutation and infection in poultry farms is crucial for early detection of novel recombinant viruses with pandemic potential and for enhancing biosecurity control.